Simple test bench for characterisation of high‐intensity discharge lamps in the frequency domain. Issue 9 (11th April 2016) - Osorio, R.; Alonso, J.M.; Balderas, R.; Vázquez, N.; Ponce, M.; Martínez, A.J.
Abstract : A simple electronic circuit for the characterisation of high‐intensity discharge (HID) lamps in the frequency domain by obtaining the transfer function of the lamp impedance is presented. The circuit uses a low cost power amplifier to apply a sinewave to the current and the voltage in the lamp. Also, this circuit employs an ordinary igniter based on a high voltage transformer. This circuit is a good alternative when a ballast designer prefers to get a lamp model from experimental Bode plots, and when a low budget is available to build a test bench to characterise HID lamps. Simulations and experimental results obtained from an HPS lamp are shown.